Parkinson’s disease impairs grip force release during a sinusoidal force tracking task - Sara Davidson; Kenneth Learman; Anson B. Rosenfeldt; Eric Zimmerman; Jay L. Alberts (Experimental Brain Research, 2026)
The generation, modulation, and release of grip force underlie skilled manual dexterity and object interaction. Advancing age and neurological disease compromise force generation; the impact of age and pathology on the dynamic control of grip force release is unclear. The aim of this project was to determine the impact of age and Parkinson’s disease (PD) on grip force generation and release. Young adults (YA, n = 10, 18–28 years), older adults (OA, n = 10, 57–77 years), and people with PD (PwPD, n = 10, 56–75 years) completed a sinusoidal force tracking task using a precision grip with their dominant hand. Maximum grip force was not different between groups, however, OA relative to YA exhibited deficits in force generation, release and amplitude scaling. Although PwPD had global declines in force control, force release was disproportionately affected compared to force generation. The ability to scale force during its generation and release was compromised by PD. Two-point discrimination of the thumb and index fingers was impaired in PwPD and was moderately correlated with force tracking accuracy and force amplitude. While aging impacts grip force generation and release similarly during a task requiring continuous grip force modulation, PD disproportionately affects grip force release compared to generation. Force amplitude progressively decreases in older adults and PwPD. Potential sources of PD deficits include neural circuitry changes between the prefrontal cortex and striatum, impaired sensorimotor integration, and altered motor unit structure and function. Additional work is focused on identifying the neural mechanism(s) underlying impaired control and regulation of grip forces in PwPD.

Grip force release is impaired in parkinson’s disease during a force tracking task - Sara Davidson; Kenneth Learman; Eric Zimmerman; Anson B. Rosenfeldt; Jay L. Alberts (Experimental Brain Research, 2025)

Older adults are impaired in the release of grip force during a force tracking task - Sara Davidson; Kenneth Learman; Eric Zimmerman; Anson B. Rosenfeldt; Mandy Koop; Jay L. Alberts (Experimental Brain Research, 2024)
Age-related changes in force generation have been implicated in declines in older adult manual dexterity. While force generation is a critical aspect of the successful manipulation of objects, the controlled release of force represents the final component of dexterous activities. The impact of advancing age on the release of grip force has received relatively little investigation despite its importance in dexterity. The primary aim of this project was to determine the effects of age on the control of force release during a precision grip tracking task. Young adults ( N = 10, 18–28 years) and older adults ( N = 10, 57–77 years) completed a ramp-hold-release (0–35% of maximum grip force) force tracking task with their dominant hand. Compared to young adults, older adults were disproportionately less accurate (i.e., less time within target range) and had more error (i.e., greater relative root mean squared error) in the release of force, compared to generation of grip force. There was a significant difference between groups in two-point discrimination of the thumb, which was moderately correlated to force control across all phases of the task. The decline in force release performance associated with advanced age may be a result of sensory deficits and changes in central nervous system circuitry.